MANET Routing Protocols: A Review - Kaur, J; Singh, G (International Journal of Computer Sciences and Engineering, 2025)
The MANET is the self-configuring network in which mobile nodes can join or leave the network any time. Due to its decentralized nature routing is the major concern or major issue on MANET. In this work properties of reactive, proactive and hybrid is highlighted and discuss in terms of discussion or concern. In this work best performing AODV protocol for path establishment for improved using bio inspire techniques.